Leadership Style Analysis In Improving Employee Performance At University - Supatmin; Hartatik; Eni Erwantiningsih; Ahmad Mukhlis (International Journal of Science, Technology & Management, 2021)
The development of world life, in general, encourages people to move towards the era of globalization which increasingly demands an increase in the standard of order in various ways.This research is a descriptive study, with a qualitative approach, the data used are primary and secondary data, with interview, observation, and documentation data collection techniques, while the data analysis method uses descriptive analysis, because in this study the author describes the leadership style and employee performance at College.The results of the study indicate that the leadership style in the economics faculty at a university is a selling leadership style because in the economics faculty the task is very high and the relationship is also very high and the leadership always provides direction and explains the results of decisions. And also the leadership style at the Faculty of Economics because his leadership puts forward good relationships and high examples and very maximum and optimal tasks.Employee performance can be said to qualify as a good employee because the employee has been conducting in the accordance job description of each and they also work following the standards of quality, quantity, and time standards set by the faculty. However, in terms of working time discipline, more serious attention must still be needed. This can be seen in the data obtained by researchers.